Defining diaspora in post-Yugoslav states - Vuković-Ćalasan, Danijela (Array, 2021)
Contemporary societies exist in the conditions of globalization, which profoundly‎ transforms them in different dimensions. Technological progress enabled‎ the significant changes in the identity dimension. This has, inter alia,‎ resulted in new opportunities for preserving identification with the country of‎ origin, increased interest in the diaspora concept in the politological and sociological‎ thought and caused new approaches and activities by the states in‎ improving relations with their diasporic communities. The former republics‎ of the SFRY, which have been making progress in building legal and institutional‎ capacities for cooperation with diasporas, are no exception. Generally,‎ all of these countries have very numerous and diverse diasporas, which have‎ usually been emerging in a long period of time. This paper analyzes the policies‎ of the states, created by the break-up of the SFRY, towards their diasporas.‎ The policies of these states are specific and they differ from one another,‎ both in defining diaspora and in legal and institutional solutions that should‎ improve diaspora’s link with the country of origin. However, the Republic of‎ Slovenia, the Republic of Croatia, Bosnia and Herzegovina, the Republic of‎ Serbia, Montenegro and the Republic of North Macedonia, have some common‎ elements as well.‎